Investigation of molecular mechanism leading to gefitinib and osimertinib resistance against EGFR tyrosine kinase: molecular dynamics and binding free energy calculation - Singh A.; Mishra A. (My University, 2025)
Tyrosine kinase (TK) is an important protein responsible for phosphorylation of variety of proteins that helps in signal transduction process in transferring signal to regulate various physiological and biochemical processes. Drugs inhibiting signal transduction pathways can be a very rational approach to inhibit cellular physiological and biochemical process. Tyrosine kinase inhibitors are a wide family of drugs that have been used successfully in cancer chemotherapy. Certain mutations around the catalytic cleft may cause conformational changes at binding site and leads to decrease in inhibitor sensitivity to TK mutants. EGFRT790M mutation is the first recognized acquired resistance after tyrosine kinase inhibitor therapy that leads to resistant to first generation TKI in about 50% of non-small cell lung carcinoma patients. Third generation EGFR-TKIs bind irreversibly to the C797, which is present in the ATP-binding pocket. The present work provides a molecular mechanism for understanding the Gefitinib and Osimertinib sensitivities with the EGFRWILD, EGFRL858R, EGFRT790M, EGFRT790M+C797S mutants using molecular modelling techniques. Changes in response against Gefitinib and Osimertinib were observed with the change of amino acids at the tyrosine kinase domain of EGFRWILD and its mutants (EGFRL858R, EGFRT790M, EGFRT790M+C797S). RMSD, RMSF and binding energies calculation well correlates with the change in clinical observation. Communicated by Ramaswamy H. Sarma. © 2022 Informa UK Limited, trading as Taylor & Francis Group.